Ishmael and Isaac: An Essay on the Divergent Moral Economies of the Qur’an and the Torah - Alam, M. Shahid (Islamic Studies, 2012)
The Torah and the Qur’an offer different conceptions of individual autonomy. These differences are best illustrated by the manner in which the two scriptures deal with the episode of Abraham’s near-sacrifice of his son. In the Torah, Abraham neither informs nor consults with Isaac about the sacrifice. In the Qur’an, Abraham seeks and receives Ishmael’s consent before proceeding with the near-sacrifice. “My son, I have seen myself sacrificing you in a dream. Consider, then, what would be your view.” Qur’an 37: 102"